Post-neoadjuvant cellular dissociation grading based on tumour budding and cell nest size is associated with therapy response and survival in oesophageal squamous cell carcinoma - Jesinghaus, Moritz; Boxberg, Melanie; Wilhelm, Dirk; Münch, Stefan; Dapper, Hendrik; Quante, Michael; Schlag, Christoph; Lange, Sebastian; Budczies, Jan; Konukiewitz, Björn; Mollenhauer, Martin; Schlitter, Anna Melissa; et al. (British journal of cancer, 2019)
Cellular Dissociation Grade (CDG) composed of tumour budding and cell nest size has been shown to independently predict prognosis in pre-therapeutic biopsies and primary resections of oesophageal squamous cell carcinoma (ESCC). Here, we aimed to evaluate the prognostic impact of CDG in ESCC after neoadjuvant therapy. We evaluated cell nest size and tumour budding activity in 122 post-neoadjuvant ESCC resections, correlated the results with tumour regression groups and patient survival and compared the results with data from primary resected cases as well as pre-therapeutic biopsies. CDG remained stable when results from pre-therapeutic biopsies and post-therapeutic resections from the same patient were compared. CDG was associated with therapy response and a strong predictor of overall, disease-specific (DSS) and disease-free (DFS) survival in univariate analysis and—besides metastasis—remained the only significant survival predictor for DSS and DFS in multivariate analysis. Multivariate DFS hazard ratios reached 3.3 for CDG-G2 and 4.9 for CDG-G3 neoplasms compared with CDG-G1 carcinomas (p = 0.016). CDG is the only morphology-based grading algorithm published to date, which in concert with regression grading, is able to contribute relevant prognostic information in the post-neoadjuvant setting of ESCC.